Population Structure of Aleurites moluccana Willd in the Tour Bajuin Waterfall Tanah Laut - Ansari, Muhammad Lutvi; Dharmono, Dharmono; Amintarti, Sri (Universitas Sebelas Maret, 2015)
South Kalimantan has a diverse flora, this can be seen from the many diverse types of trees.Growing human populations, it also increases the demand for availability of land for settlements that cause a reduction in forest green areas impact the decline of biodiversity especially Aleurites moluccana Willd plant in South Kalimantan forests. The purpose of this research is to assess the population structure of Aleurites moluccana Willd In The Tour Bajuin Waterfall Tanah Laut. The method used was survey method 10 m x 10 m quadrant for the seedling, sapling, pole and tree, systematically in region 1 at the top of the waterfall Bajuin and region 2 under the waterfall Bajuin each 500 m x 250 m quadrant. Results research population structure of Aleurites moluccana Willd in region 1 density of seedling 96 ind/Ha, sapling 60 ind/Ha, pole 44 ind/Ha and tree 64 ind/Ha, while in region 2 density of seedling 260 ind/Ha, sapling 144 ind/ha, pole 116 ind/ha and tree 228 ind/ha. In region 1 and region 2 number of young individu much more older individual thus forming the wide base of the pyramid, show the population is growing.Keywords: Population structure, Aleurites moluccana Willd